Smart-Specialization of the Agro-Industrial Complex in the Context of Digital Transformation of Regional Economic Systems - Anna M Kulik; Elena A Lavrinenko; Julia V Lyshchikova; Elena A Stryabkova (ETIKONOMI, 2021)
This article presents a domestic and foreign experience of "smart specialization" in agriculture in the digital economy. The method of calculating the indicators of digital maturity of the agro-industrial complex is considered. The forecast of indicators value of the agro-industrial digital maturity is presented until 2030. The article proposes a mechanism for adapting the smart specialization in agriculture. We consider it appropriate to introduce an online digital platform in agriculture, which allows creating conditions for interaction between sellers and buyers of regional agricultural machinery and related products. Based on the presented mechanism of adaptation of "smart specialization "in the field of agro-industrial complex, it should be noted that" smart specialization" is aimed at using the links that arise between the regions of economic activity. The priority areas of activity of the agro-industrial complex are presented.JEL Classification: L52, Q16, R11How to Cite:Kulik, A. M., Lavrinenko, E. A., Lyshchikova, J. V., & Strybkova, E. A. (2021). Smart-Specialization of the Agro-Industrial Complex of Digital Transformation of Regional Economic System. Etikonomi, 20(2), xx– xx. https://doi.org/10.15408/etk.v20i2.22015.